2006
DOI: 10.1111/j.0021-9029.2006.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Threat in Attitudes Toward Affirmative Action and Its Beneficiaries1

Abstract: This set of two studies employed the integrated threat theory to examine attitudes toward affirmative action (AA). The first study found that opposition to the policy of AA was predicted by realistic threats, symbolic threats, and personal relevance; while attitudes toward the beneficiaries of AA were predicted by three of the four threat variables (symbolic threats, intergroup anxiety, and negative stereotypes), and in-group identity. The second study replicated and expanded on the first study and found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 43 publications
3
68
0
3
Order By: Relevance
“…As previously indicated, studies of integrated threat theory show that perceived realistic and symbolic threats to the ingroup are consistently related to intergroup anxiety (Berrenberg et al, 2002;Corenblum & Stephan, 2001;Renfro et al, 2006;W. G. Stephan et al, 1999;W.…”
Section: Attitudes and Related Cognitionsmentioning
confidence: 87%
See 1 more Smart Citation
“…As previously indicated, studies of integrated threat theory show that perceived realistic and symbolic threats to the ingroup are consistently related to intergroup anxiety (Berrenberg et al, 2002;Corenblum & Stephan, 2001;Renfro et al, 2006;W. G. Stephan et al, 1999;W.…”
Section: Attitudes and Related Cognitionsmentioning
confidence: 87%
“…Several studies have found that strength of identity with the ingroup is positively correlated with intergroup anxiety (Aberson & Gaffney, 2008;Corenblum & Stephan, 2001;Renfro et al, 2006;Suzuki-Crumly & Hyers, 2004). Similarly, considering the ingroup to be highly distinctive has also been found to be positively correlated with intergroup anxiety (González, Sirlopú, & Kessler, 2010), perhaps because ingroup members are worried that their feeling of distinctiveness will be undermined during interactions with outgroup members.…”
Section: Personality Traits and Personal Characteristicsmentioning
confidence: 99%
“…Although the relationship between intergroup threat and negative responses has been extensively studied, only a small number of studies have focused on how intergroup threat influences positive behavior (Renfro, Duran, Stephan, & Clason, 2006;Sawires & Peacock, 2000). Logically, negative responses to threat not only entail the promotion of direct intergroup conflicts, such as aggression, discrimination and stereotyping, but also encompass an indirect reduction in positive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Logically, negative responses to threat not only entail the promotion of direct intergroup conflicts, such as aggression, discrimination and stereotyping, but also encompass an indirect reduction in positive behavior. For instance, when exposed to threat, individuals responded by opposing policies favoring the out-group (Renfro, et al, 2006;Sawires & Peacock, 2000). The present research focuses on how intergroup threat may affect out-group helping behavior, which is particularly important in social life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers have found that people respond to intergroup threat by opposing a policy that is advantageous to out-group members, for example, affirmative action in the United States (Renfro, Duran, Stephan, & Clason, 2006). This kind of opposition, which stems from intergroup threat, can impede the implementation of a positive policy, and is likely to restrict the ability of the out-group members to move forward.…”
mentioning
confidence: 99%